Staphylococcal scalded skin syndrome in a preterm infant - Demirel, Gamze; Şahin, Şifa; Karavar, Hande Nur; Gündoğdu, Semra; Vatansever, Binay; Yüksel, Mavişe; Taştekin, Ayhan (Jpms Publisher, 2017)
A male infant was delivered by cesarean section at 26 weeks and 3 days gestational age and weighed 1020 grams. Apgar scores were 7 and 8 at 1st and 5th minutes, respectively. The baby was hospitalized for prematurity, and given one dose of surfactant therapy on the first day of life. Empirical ampicillin and gentamicin therapy was started on the first day of life and continued for ten days. He also received high-flow oxygen through nasal cannula. The patient had neither clinical nor culture-proven sepsis attacks. On the 25th day of his life, the patient developed diffuse blanching erythema which started around the nose followed by appearance of bullous lesions on the extremities, neck and upper back regions (Figure 1).
WOS: 000418094200002
Keywords: Staphylococcal Scalded Skin Syndrome; Preterm Infant